Microstructure, Corrosion and Wear Behaviors of Electroless (NiP-TiC-SiC) Nanocomposite Coating on Acrylonitrile Butadiene Styrene Substrate - Rusul Khalid Alhamad; Abbas Khammas Hussein; Laith Kais Abbas (Surfaces)
A variety of NiP-TiC-SiC nanocomposite coatings were deposited to acrylonitrile–butadiene–styrene (ABS) substrates at varying plating periods and bath temperatures using electroless plating. A field emission scanning electron microscope (FESEM) demonstrates the production of various coating morphologies. Morphology analysis of the deposit coatings shows homogenous, compact, and nodular structured coatings free of any apparent defects in most deposition conditions, except at extra high-temperature deposition baths, some gas bubbles under the coating layers were seen. The patterns of X-ray diffraction (XRD) illustrate nickel peaks at 44.5 which relates to Ni (111). Energy-dispersive X-ray spectroscopy (EDX) data show that the coating’s main constituents are nickel, phosphorus, and nanoparticles. According to the results of the contact angle test, the potentiodynamic polarization, and the impedance spectroscopy (EIS) tests conducted in (3.5%) of NaCl by weight at (25 °C), the nanocomposite coating that was created at 90 min and 75 °C exhibited the best hydrophobic qualities and corrosion resistance. The coating formed at 30 min and 75 °C illustrates the best hardness value. The adhesion force was calculated using the ASTM D 3359 method (B). The findings demonstrate that the coating made under the following deposition conditions, 30 min at 75 °C, 30 min at 95 °C, and 90 min at 75 °C, produces the best bonding strength between the coating and ABS substrate (standard classification 5B); however, the complete gas bubble rejection process from the substrate is rendered difficult by deposition times longer than 30 min in a bath over 85 °C, which decreases the adhesion between NiP-TiC-SiC and the acrylonitrile–butadiene–styrene substrate. The wear rate shows a direct relationship with the coefficient of friction rather than hardness, and the coated prepared at 90 min at 75 °C offers a lower wear rate and coefficient of friction.